EMPLOYEE PERFORMANCE ANALYSIS AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF MUSI RAWAS REGENCY - Susanto, Yohanes; Yuliana, Yuliana (Sosiohumaniora, 2021)
This study aims to analyze the factors that affect employee performance at the Regional Financial and Asset Management Agency, Musi Rawas Regency, South Sumatra. This research is a quantitative study with a total population of 60 respondents. The results of the analysis show that the variables of Competence, Leadership and Motivation simultaneously have a positive and significant effect on performance. Moreover, Competence (X1) Leadership (X2) and Motivation (X3) partially have a positive and significant effect on employee performance (Y). However, the Leadership variable has a very dominant influence on performance. It is recommended that the performance of employees at the Regional Financial and Asset Management Agency of Musi Rawas Regency to be improved. The role of leadership can also be used as a benchmark for the success of a team’s work in public services, delegation of authority and supervision. It is also recommended that the leader’s task evaluation be carried out periodically. In addition, efforts to improve employee competence are a strategic step in increasing employee motivation.